2014
DOI: 10.1007/s13197-014-1435-2
|View full text |Cite
|
Sign up to set email alerts
|

Thin layer convective air drying of wild edible plant (Allium roseum) leaves: experimental kinetics, modeling and quality

Abstract: The present study deals with the valorization of an edible spontaneous plant of the Tunisian arid areas: Allium roseum. This plant is traditionally used for therapeutic and culinary uses. Thin-layer drying behavior of Allium roseum leaves was investigated at 40, 50 and 60°C drying air temperatures and 1 and l.5 m/s air velocity, in a convective dryer. The increase in air temperature significantly affected the moisture loss and reduced the drying time while air velocity was an insignificant factor during drying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
(78 reference statements)
4
12
0
Order By: Relevance
“…For this purpose, in the case of hot air drying: equation 9 (Eq. (9)) linking temperature to the effective moisture diffusivity was used (Murthy and Manohar, 2014;Ben Haj Said et al, 2015). However, in the case of microwave drying, the process is not isothermal and temperature cannot be measured (Dadalı et al, 2007;Özbek and Dadali, 2007).…”
Section: Mathematical Modelling Of Drying Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, in the case of hot air drying: equation 9 (Eq. (9)) linking temperature to the effective moisture diffusivity was used (Murthy and Manohar, 2014;Ben Haj Said et al, 2015). However, in the case of microwave drying, the process is not isothermal and temperature cannot be measured (Dadalı et al, 2007;Özbek and Dadali, 2007).…”
Section: Mathematical Modelling Of Drying Curvesmentioning
confidence: 99%
“…However, at an advanced drying process stage, we observed a reduction of the energy absorbed by the product surface. This is due to the lower water content of the partially dried product and to the dry surface, which prevents the penetration of heat and the migration of water (Ben Haj Said et al, 2015).…”
Section: Drying Curvesmentioning
confidence: 99%
“…In this regard, some empirical models have been proposed to describe the kinetics of dehydration in food products [17,18]. No complete model has been found to predict the moisture content over the entire drying time under different conditions and product types [19]. The theoretical model that has been used most in drying is Fick's second law with an Arrhenius equation, since diffusivity is dependent on temperature [20] and it is considered as the mechanism of moisture transport in various roasting studies.…”
Section: Introductionmentioning
confidence: 99%
“…The most relevant aspects of drying and roasting technology are the mathematical modeling of processes and the experimental method [11]. In the drying process, experimental data are described while using different models, which are widely cited in the scientific literature due to the results obtained to describe drying kinetics [19]. The simulation of the roasting process through mathematical models is a widely used tool, since it helps to minimize operating problems, such as high energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum value of the activation energy for moisture diffusion in the experiments conducted in this study was found to be 61.28 KJ/mol for 60 mm bed height and 6 mm dice thickness. The values of activation energy were found to be higher than those of 8.3143 kJ/mol for tomato [22], 46.80-52.68 kJ/mol for rosy garlic leaves [23], 57.36 kJ/mol for Moroccan rosemary leaves [24], 32.65 kJ/mol for banana slices [25], 13.48-16.50 kJ/mol for sweet potatoes slices [18], and 12.50 kJ/mol for drumstick leaves [26] dried under similar conditions. About the same values were obtained for konjac dices as those of 30.64 kJ/mol for persimmon slices [27], 30.00 kJ/mol for bacon slices [17], and 22.01-30.99 kJ/mol for green peas [28] dried under similar conditions.…”
Section: Moisture Diffusivity and Activation Energymentioning
confidence: 61%